A review on membrane fouling: membrane modification - TUNABOYLU, BAHADIR (DESALINATION PUBL, 2021)
Membrane separation has become a prevalent technique in water and wastewater treatment. However, fouling is still the most challenging issue in case of membranes. Fouling causes flux decline, loss in rejection performance, increased energy consumption, etc. Different modification techniques have been applied to mitigate fouling on the membrane surface. In this study, the insights for state-of-the-art approaches in membrane modification using nanoparticles, organic modifiers such as hydrophilic, amphiphilic, and zwitterionic materials were critically reviewed. Detailed information about the methods blending, interfacial polymerization, grafting, coating, etc. were provided. Furthermore, the effects of membrane modification on membrane morphology and membrane performance were discussed. Finally, the obstacles for the scale-up of the studied techniques are analyzed.
Keywords: Membrane fouling; Membrane modification; Nanoparticles; Hydrophilic modifiers; Amphiphilic modifiers; Zwitterionic modifiers; HOLLOW-FIBER MEMBRANE; ANTIFOULING NANOFILTRATION MEMBRANE; ASSISTED GRAFT-POLYMERIZATION; REVERSE-OSMOSIS MEMBRANES; WASTE-WATER TREATMENT; IN-SITU FORMATION; ULTRAFILTRATION MEMBRANES; SURFACE MODIFICATION; GRAPHENE OXIDE; SILVER NANOPARTICLES